Experimental Design-Based Response Surface Methodology Optimization for Synthesis of β-Mercapto Carbonyl Derivatives as Antimycobacterial Drugs Catalyzed by Calcium Pyrophosphate. (6th March 2014) - Abrouki, Younes; Anouzla, Abdelkader; Loukili, Hayat; Bennazha, Jamal; Lotfi, Rabiaâ; Rayadh, Ahmed; Bahlaoui, My Abdellah; Sebti, Saïd; Zakarya, Driss; Zahouily, Mohamed
Abstract : A simple protocol for the efficient preparation of β -mercapto carbonyl derivatives as antimycobacterial drugs has been achieved via Thia-Michael reaction between chalcones derivatives and thiols in the presence of calcium pyrophosphate as a heterogeneous catalyst under mild reaction conditions. The central composite design was used to design an experimental program to provide data to model the effects of various factors on reaction yield ( Y ) . The variables chosen were catalyst weight X 1, reaction time X 2, and solvent volume X 3 . The mathematical relationship of reaction yield on the three significant independent variables can be approximated by a nonlinear polynomial model. Predicted values were found to be in good agreement with experimental values. The optimum reaction conditions for reaction model (chalcone and thiophenol) obtained by response surface were applied to other substrates. This procedure provides several advantages such as high yield, clean product formation, and short reaction time.